PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN DANA ALOKASI UMUM (DAU) TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN KETAPANG - B61110047, M U H A D I (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT This study aims to identify and analyze the influence of local revenue (PAD ) and the General Allocation Fund ( DAU ) to economic growth in Ketapang . This study uses secondary data (time series) from 2000 until 2012 . The method of analysis used in this study is a quantitative method , with regression testing to test the classical assumption before getting the best research model . The variables in this study is the revenue ( PAD ) , the General Allocation Fund ( DAU ) as the independent variable and Economic Growth as the dependent variable . The population in this study is a sample of Ketapang in researchobject. Results of this study demonstrate that simultaneous Revenue and General Allocation Fund had no significant effect on economic growth in Ketapang this can be explained in the R square of 10.58 % variable economic growth can be explained by the independent variables exist that PAD and DAU no effect on economic growth . While the remaining 80.42 % is influenced by other variables that are not explained by the model of this study . Partial variable revenue ( PAD ) had no significant effect on economic growth , as well as variable General Allocation Fund ( DAU ) had no significant effect on economic growth in Ketapang . Thus the district / city government General Allocation Fund as a result of the fiscal equalization tool fiscal gap , which needs DAU an area determined by the needs of the region ( fiscal needs) and potential areas ( fiscal capacity) that determine the composition of the fulfillment of economic growth, especially in Ketapang . Keywords : Revenue , General Allocation Fund , Economic Growth .